2010
DOI: 10.1080/20932685.2010.10593062
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Intentions of Fashion Marketing Interns: The Impact of Work-related Attitudes and Behaviors**

Abstract: Fashion marketing/retailing is a major employment sector and driver of economic activity on a global level. Michael

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Instead, they suggested that researchers, who are interested in motivations, should develop motivational structures and benefit structures independently in separate factor analyses. Because of the study of tourism and shopping tends to use local variable context and gather the subjects from the study of travel motivation with characteristic of the destination from Frochot (2005) in Scotland, Royo-Vela (2009), Molera and Albaladejo (2007) and Perales (2002) in Spain, Kastenholz, Davis, and Paul (1999) in Portugal and Pesonen, Komppula, and Laukkanen (2009) in Finland, and the literature review of Hurst, Niehm, and Park (2010) based on earlier literature shows that tourists have several similarities: They are most often motivated by opportunities to learn and explore nature or different cultures, participate in outdoor activities, and search for peace and solitude. They may expect family togetherness, peace and quietness, a friendly reception, a change from their routine and good food.…”
Section: Tourism and Tourist Shoppingmentioning
confidence: 99%
“…Instead, they suggested that researchers, who are interested in motivations, should develop motivational structures and benefit structures independently in separate factor analyses. Because of the study of tourism and shopping tends to use local variable context and gather the subjects from the study of travel motivation with characteristic of the destination from Frochot (2005) in Scotland, Royo-Vela (2009), Molera and Albaladejo (2007) and Perales (2002) in Spain, Kastenholz, Davis, and Paul (1999) in Portugal and Pesonen, Komppula, and Laukkanen (2009) in Finland, and the literature review of Hurst, Niehm, and Park (2010) based on earlier literature shows that tourists have several similarities: They are most often motivated by opportunities to learn and explore nature or different cultures, participate in outdoor activities, and search for peace and solitude. They may expect family togetherness, peace and quietness, a friendly reception, a change from their routine and good food.…”
Section: Tourism and Tourist Shoppingmentioning
confidence: 99%